Unraveling the Nectar Secretion Pathway and Floral-Specific Expression of SWEET and CWIV Genes in Five Dandelion Species Through RNA Sequencing - Sivagami-Jean Claude; Sunmi Park; Seong-Jun Park; SeonJoo Park (Plants)
Taraxacum, a genus in the Asteraceae family, is widely distributed across temperate regions and plays a vital ecological role by providing nectar and pollen to pollinators during the early flowering season. Floral nectar is a key reward that plants use to attract pollinators, and its production is tightly regulated by genes such as SWEET sugar transporters and CELL WALL INVERTASE (CWIN), which govern sugar efflux and hydrolysis. Despite their ecological importance, the molecular mechanisms underlying nectar secretion in Taraxacum remain poorly understood. In this study, we performed RNA sequencing of flower tissues from five Taraxacum species—T. coreanum, T. monogolicum, T. ohwianum, T. hallaisanense, and T. officinale—to investigate the expression of nectar-related genes. De novo transcriptome assembly revealed that T. coreanum had the highest unigene count (74,689), followed by T. monogolicum (69,234), T. ohwianum (64,296), T. hallaisanense (59,599), and T. officinale (58,924). Functional annotation and phylogenetic analyses identified 17 putative SWEET and 18 CWIN genes across the five species. Differential gene expression analysis highlighted tarSWEET9 and tarCWIN4 as consistently up-regulated during the flowering stage. Quantitative PCR in T. officinale further validated that tarSWEET9, tarCWIN4, tarCWIN6, and tarSPAS2 show significant expression during floral development but are down-regulated after pollination. These genes are likely central to the regulation of nectar secretion in response to pollination cues. Our findings suggest that T. officinale may have evolved to have an efficient, pollinator-responsive nectar secretion system, contributing to its global adaptability. This study sheds light on how pollinator interactions influence gene expression patterns and may drive evolutionary divergence among Taraxacum species.